The utility of consensus approaches in virtual drug discovery - Houston, Douglas (Henry Stewart Talks, 2019)
Virtual screening for drug discovery, How docking programs work, The concept of consensus scoring, The concept of consensus docking, The reliability of consensus docking, Effect of ligand flexibility on docking success rate, Virtual screening to identify lead-like molecules active against specific drug targets